1998
DOI: 10.1046/j.1471-4159.1998.70010292.x
|View full text |Cite
|
Sign up to set email alerts
|

Congo Red Inhibits Proteoglycan and Serum Amyloid P Binding to Amyloid β Fibrils

Abstract: Various data suggest that Alzheimer's disease results from the accumulation of amyloid /3 (Aj3) peptide fibrils and the consequent formation of senile plaques in the cognitive regions of the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…After 24 h of incubation, soluble A␤ was separated from aggregated and fibrillar peptide by centrifugation (23,24). Different chondroitin sulfate-derived saccharides had variable effects on the amount of pelletable aggregates detected with greater effects seen for A␤42 (Fig.…”
Section: Induction and Morphology Of A␤ Fibril In The Presence Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…After 24 h of incubation, soluble A␤ was separated from aggregated and fibrillar peptide by centrifugation (23,24). Different chondroitin sulfate-derived saccharides had variable effects on the amount of pelletable aggregates detected with greater effects seen for A␤42 (Fig.…”
Section: Induction and Morphology Of A␤ Fibril In The Presence Ofmentioning
confidence: 99%
“…The GAG binding site on the A␤ peptide has been investigated using amino acid substitution of the A␤1-28 peptide and as a function of aggregation state (22,23). These studies have demonstrated that although electrostatic interactions through basic amino acids contribute to GAG binding, nonionic interactions, such as hydrogen bonding and van der Waals packing, play a role in GAG-induced A␤ folding and aggregation (22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This mutually disadvantageous interaction holds the amyloid components in a trap and strengthens the amyloid generating and stabilizing process which eventually leads to widespread neuronal loss. The inhibition of the bond between SAP and Aβ results in free SAP and Aβ can be proteolytically cleaved and cleared from the brain [28,29,63]. Free SAP can be removed from the CNS by the active effl ux transport demonstrated here.…”
Section: Discussionmentioning
confidence: 77%
“…olfactory neuroblasts) remains to be an issue. Congo red, which is known to stain amyloid deposits for several decades [216][217][218], stimulated the ongoing search for small markers of Aβ levels. Yet, the detailed mechanism of Congo red binding is still a subject of investigations [219][220][221][222][223][224].…”
Section: Diagnostics -Markers For Admentioning
confidence: 99%